Implementasi Sistem Pengendalian Internal dan Moralitas Individu Untuk Mengantisipasi Kecurangan (Fraud) Biaya Produksi (Studi Kasus pada PT. Indra Karya (Persero) – Divisi Survey dan Investigasi) - Ramadhania, Eno Dwi; Maslichah, Maslichah; Hidayati, Irma (Universitas Islam Malang, 2024)
This research was conducted to determine implementation of internal control system and individual morality to anticipate production cost fraud (a case study of a PT. Indra Karya (Persero) – Survey and Investigation Division). This research uses descriptive qualitative methods. This research uses the Fraud Triangle Theory as the basis for its research. The result of this research shows that internal control system and individual morality have effect on anticipate production cost fraud. PT. Indra Karya (Persero) – Survey and Investigation Division has implemented a good internal control system and individual morality.Keywords: Fraud, internal control system, individual morality.